Build it and they will come: How does a new public transit station influence building construction?. (April 2022) - Champagne, Marie-Pier; Dubé, Jean; Barla, Philippe
Abstract: The aim of the paper is to investigate the impact of the extension of a metro line on real estate development. An empirical analysis focuses on the relationship between proximity to new stations and the number of new constructions, both commercial and residential, from the announcement of the project. A matching approach based on pre-project characteristics is developed using a 2-km zone around the stations based on a hexagonal grid. The potential effects are separated into three distinct periods in order to identify the presence of speculation, anticipation and adjustment effects, i.e., during the announcement, the construction, and the opening of the line. The results suggest that new commercial buildings development occurs within 750 m of stations at the end of the process, while new residential development is primarily concentrated between 1000 and 1250 m and emerges at the beginning of the process. The joint increase in new residential and commercial constructions within direct proximity to the stations, after the service is in operation, underlines the growth of mixed-use neighborhoods, accommodating both residential and commercial activities. Highlights: This paper aims to study the impact of a metro line on real estate development. Results suggest that new metro stations influence the construction of new buildings. Commercial constructions emerge mostly post-opening, within 750 m of stations. Residential constructions showed anticipation effects within 1000 and 1250 m. Residential buildings erect 1000 and 1250 m before, and within 500 m after.